Mechanical Thrombectomy System for the Treatment of Intermediate-Risk Acute Pulmonary Embolism: The CLEAR Study - Wenguang Zhang; Tao Hu; Song Ding; Zhouming Wang; Tao Zhang; Hongyao Hu; Xin Fang; Honggang Pang; Mingjin Guo; Bo Yu; Hui Zhuang; Nuofu Zhang; et al. (Cardiovascular Innovations and Applications)
Background: Mechanical thrombectomy is effective and safe for treating pulmonary embolism (PE). Although the Tendvia mechanical thrombectomy system has been validated in pigs, further evidence supporting its use in PE treatment is needed. Objectives: This study was aimed at evaluating the safety and efficacy of the Tendvia system for intermediate-risk acute PE. Methods: This prospective, single-arm, multicenter study included symptomatic patients with acute PE ≥18 years of age, with a right ventricular (RV)/left ventricular (LV) diameter ratio ≥0.9. The primary efficacy endpoint was the change in RV/LV diameter ratio from baseline to 48 hours postprocedure. The primary safety endpoint was the incidence of major adverse events (AEs), device-related death, 48-hour postprocedure major bleeding, pulmonary vascular injury, and cardiac injury. The secondary efficacy endpoint was the systolic pulmonary arterial pressure (PAP) change from pre- to postprocedure. Secondary safety endpoints included 48-hour postprocedure clinical deterioration, device-related AEs, and symptomatic PE recurrence within 30 days. Results: Of 127 patients at 15 centers with intermediate-risk acute PE who underwent mechanical thrombectomy with the Tendvia system (September 2021 to December 2022), 123 underwent analysis. The mean RV/LV diameter ratio decrease was 0.42 ± 0.28; 95% CI: 0.37–0.47; P < 0.001. The bleeding risk was low, and the hospitalization duration was short. One patient experienced clinical deterioration within 48 hours, and none experienced major AEs, device-related pulmonary vascular injury, cardiac injury, or major bleeding within 48 hours. Seven patients had 11 serious AEs within 30 days. The mean systolic PAP decrease was 7.10 mmHg (P < 0.001). Conclusion: The Tendvia system for mechanical thrombectomy is safe and effective for intermediate-risk acute PE, in agreement with the safety profiles in other studies.